2022
DOI: 10.1111/cns.13827
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GRK6 alleviates chronic visceral hypersensitivity through downregulation of P2Y6 receptors in anterior cingulate cortex of rats with prenatal maternal stress

Abstract: Aims: Visceral hypersensitivity is a major clinic symptom in patients with irritable bowel syndrome (IBS). Anterior cingulate cortex (ACC) is involved in processing the information of pain. Both G protein-coupled receptor kinase 6 (GRK6) and P2Y purinoceptor 6 (P2Y6) are associated with neuroinflammation and pathological pain. The aim of this study was to investigate the interaction between GRK6 and P2Y6 in ACC in the development of visceral hypersensitivity of adult offspring rats with prenatal maternal stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…Previous studies have shown that unilateral ACC injection of drugs can relieve chronic visceral pain and cause less harm to animals. 29 , 60 This was confirmed by our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that unilateral ACC injection of drugs can relieve chronic visceral pain and cause less harm to animals. 29 , 60 This was confirmed by our results.…”
Section: Discussionsupporting
confidence: 91%
“…In multiple animal models of chronic visceral pain, the ACC show dramatically activation. 25 29 The ACC contributes to the development of chronic visceral pain by regulating the function of diverse molecules and neural circuits. 14 , 30 34 …”
Section: Introductionmentioning
confidence: 99%
“…At each injection site, the needle was left in place for 10 to 15 minutes after the completion of the injection to allow the viral spread, and subsequently, it was slowly withdrawn. Because unilateral injection of the virus can change pain behavior fully 35 , 37 and bilateral injections might cause more damage to the brain tissue than unilateral injection, the unilateral injection (right hemisphere) was performed in this study.…”
Section: Methodsmentioning
confidence: 99%